HUBUNGAN KONSELING DAN PENGETAHUAN IBU NIFAS TERHADAP PENGAMBILAN KEPUTUSAN DALAM BER-KB - Putri Adinda; Nisa Kartika Ningsih; Silvia Mariana; Dwi Haryanti (Jurnal Kesehatan dan Pembangunan, 2026)
Indonesia has a policy to control population growth, including through the Family Planning (KB) program. KB is an effort made by humans to intentionally regulate pregnancy in the family without violating the law and Pancasila morals for family welfare (Maritalia, 2017). The purpose of this study was to determine the Relationship Between Counseling and Knowledge of Postpartum Mothers on Decision Making in Family Planning in the Working Area of ??the Paal V Community Health Center in Jambi City in 2026. This type of research is a descriptive analytical study with a Crosssectional approach conducted in the Working Area of ??the Paal V Community Health Center in Jambi City in 2026. The Independent Variables are Counseling and Knowledge, and the Dependent Variable is Decision Making. The population in this study were 255 postpartum mothers at the Paal V Community Health Center in Jambi City. The sample determination refers to the Random Sampling technique with the Slovin formula of 38 respondents. The results of the study showed that most postpartum mothers had received family planning counseling (31 respondents (81.6%), while 7 respondents (18.4%) had not. 17 respondents (44.7%) had sufficient knowledge, and 10 respondents (26.4%) had good knowledge. 34 respondents (89.5%) decided to use family planning, and 4 respondents (10.5%) decided not to use family planning. The conclusion of this study is that there is a relationship between counseling and knowledge on family planning decision-making in the work area of ??the Paal V Community Health Center in Jambi City, with a p-value of 0.02 (p <0.05) for counseling and 0.03 (p <0.05) for knowledge.